BOVINE LUMPY SKIN DISEASE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
An analysis of literature data and the results of our own research on the characteristics of the causative agent of bovine lumpy dermatitis (LD), distribution, clinical signs, cultivation, diagnosis and prevention of the disease are presented.